The cost-efficiency and productivity growth of euro area banks - Ivan Huljak; Reiner Martin; Diego Moccero (European Central Bank (ECB), 2019)
We use an industrial organisation approach to quantify the size of Total Factor Productivity Growth (TFPG) for euro area banks after the crisis and decompose it into its main driving factors. In addition, we disentangle permanent and time-varying inefficiency in the banking sector. This is important because lack of distinction may lead to biased estimates of inefficiency and because the set of policies needed in both cases is different. We focus on 17 euro area countries over the period 2006 to 2017. We find that cost efficiency in the euro area banking sector amounted to around 84% on average over the 2006 to 2017 period. In addition, we observe that Total Factor Productivity growth for the median euro area bank decreased from around 2% in 2007 to around 1% in 2017, with technological progress being the largest contributor, followed by technical efficiency. Given the need to boost productivity and enhance profitability in the euro area banking sector, these findings suggests that bank's efforts in areas such as rationalisation of branches, digitalisation of business processes and possibly mergers and acquisitions should be intensified.
Keywords: C23; D24; G21; 330; euro area; banking sector; financial stability; bank productivity; total factor productivity; cost-efficiency frontier; panel data; time-varying inefficiency; permanent inefficiency